Pengelolaan Kas, Piutang, dan Hutang Yang Efektif Sebagai Upaya Meningkatkan Profitabilitas Perusahaan - Kusuma, Fanesa Putra Adri; Winarko, Sigit Puji; Zaman, Badrus (FEB Universitas Maritim Semarang, 2024)
Profitability is a company's calculation in seeking profits so that the company can sustain its operational activities. This research aims to assist companies in managing cash, accounts receivable, and debts effectively in order to increase the company's profitability. The research employed a descriptive analysis approach. The Subject and object used in this study is PT Fokus Cory Logistik located in Malaka Sari, Jakarta. The results of this study are (1) Cash turnover in the 2020-2022 period has good enough criteria so that this cash turnover has a positive effect on the company's profitability. (2) The turnover of receivables in the 2020-2021 period had a poor turnover due to the payment of receivables for more than one month, resulting in a decrease in the percentage of profitability even though the turnover of receivables increased. (3) The debt ratio that occurred in 2020 and 2022 was considered good while in 2021 it was considered not good because the percentage was above the industry criteria, this ratio had a significant effect on profitability because a large enough debt would result in an increase in the percentage of profitability.